Evaluation of a health promotion program based on Community-based Participatory Research for older adults at risk for metabolic syndrome: a mixed methods study - Juhyeon Yang; Bohyun Park (BMC Public Health)
Abstract Background This study aimed to evaluate the effects of a health promotion program developed using Community-Based Participatory Research (CBPR) for older adults at risk for developing metabolic syndrome in rural areas of South korea. Methods The methodology of this study is a mixed method using embedded design. A non-random controlled trial (28 in the experimental group and 36 in the control group) for the quantitative study and a qualitative content analysis for the qualitative study were used. Results After the health promotion program, health promotion behavior (exercise and physical activity, cognitive maintenance function, positive acceptance) and physiological indicators related to metabolic syndrome (fast blood sugar, triglyceride, and body mass index) were significantly improved. At the intrapersonal level, positive changes regarding participants’ bodies, daily life, and emotional satisfaction were noted. At the interpersonal level, participants’ social support and sense of community improved. Conclusions This health promotion program was based on the Social Ecological Model and was developed using CBPR. Changes in some indicators at the individual and interpersonal levels were identified through the quantitative study, while specific changes at the individual, interpersonal, and community levels were identified in the qualitative study. Manuals and an assessment tool must be developed to encourage wider use of CBPR.